The Tacit Mystery: Reconciling Different Approaches to Tacit Knowledge - Muñoz-Canales, C (Palgrave Macmillan Ltd., 2015)
In the management literature, tacit knowledge has been conceptualised in partial, divergent, and contradictory ways. This paper reconciles these different approaches by explaining how they address different aspects of the theory of tacit knowing developed through the seminal work of Michael Polanyi. To clarify Polanyi s work, we provide a more inclusive theoretical framework for scholars concerned with the creation and transfer of knowledge. Using this framework, we examine the implications for theory and practice of these different conceptualisations and suggest areas for future research. We conclude by proposing that new insights can be gained by reconsidering the concepts of knowing, tacit integration and indwelling where tacit knowing is developed by practical immersion. © 2015 Operational Research Society Ltd. All rights reserved.